Design and validation of a Primary Reading Proficiency Test (PCL-P) - Trimiño-Pérez, Laura; Hurtado-Reina, Jone; Velasco, Erlantz; Martinez, Alaitz (Frontiers in Language Sciences, 2024)
Reading proficiency is one of the most important skills to be developed by students at school. However, the data on reading proficiency performance in Spanish schoolchildren show a downward trend. Thus, to measure this performance, a reading proficiency assessment test has been developed for Primary School students (PCL-P). Based on a multilevel model (executive, functional, instrumental, and epistemic), the test content is evaluated by 5 pedagogical and linguistic experts (inter-judge agreement: Fleiss´ Kappa was .88). After that, it is applied to a sample of 216 students (6 to 12 years old) of the autonomous community of the Basque Country. Cronbach's alpha was .83. On the other hand, the exploratory factor analysis (principal components method and Varimax rotation) results in 5 factors explaining 59% of the variance: 1) word and text recognition and structural understanding; 2) evaluation and critical reflection of information for the creation of new ideas; 3) advanced/deep reading strategies; 4) phonological awareness; and 5) structural understanding of language and detection of key elements. In conclusion, the PCL-P is a valid instrument for the assessment of reading proficiency in Primary.